2021
DOI: 10.1111/bcpt.13683
|View full text |Cite
|
Sign up to set email alerts
|

Benchmark dose and the adverse effects of exposure to pendimethalin at low dose in female rats

Abstract: Pendimethalin (PND) is a dinitroaniline herbicide widely used to control broadleaf and annual grasses. Although the acute oral toxicity of PND is >5 g/kg b.wt. in humans (LD50 for rats >5000 g/kg b.wt.), it has been classified as a possible human carcinogen. It is still used in agriculture so agricultural workers and their families, as well as consumers, can be exposed to this herbicide. The present study is the first report investigating the dose–response effect using the benchmark dose (BMD) and the adverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 98 publications
(233 reference statements)
0
7
0
Order By: Relevance
“…The World Health Organization (WHO) and United Nations Environment Programme (UNEP) report that pesticides pose a major threat to human health through direct or indirect exposure, with more than 26 million people suffering from pesticide poisoning and nearly 220,000 deaths each year [ 63 ]. In addition to the common toxic mechanism, neonicotinoids and organophosphate pesticides promote free radical production and can alter the oxidant–antioxidant balance when exposed to very low levels [ 8 , 40 , 64 ]. The human body has various defense mechanisms to protect against free radical species (FRS)/reactive oxygen species (ROS) damage, including enzymatic and nonenzymatic pathways [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The World Health Organization (WHO) and United Nations Environment Programme (UNEP) report that pesticides pose a major threat to human health through direct or indirect exposure, with more than 26 million people suffering from pesticide poisoning and nearly 220,000 deaths each year [ 63 ]. In addition to the common toxic mechanism, neonicotinoids and organophosphate pesticides promote free radical production and can alter the oxidant–antioxidant balance when exposed to very low levels [ 8 , 40 , 64 ]. The human body has various defense mechanisms to protect against free radical species (FRS)/reactive oxygen species (ROS) damage, including enzymatic and nonenzymatic pathways [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on their dose, duration, and mode of action, pesticides can cause various types of liver damage, such as inflammation, necrosis, fibrosis, and tumors. Histopathological studies in laboratory animals can reveal the morphological and cellular changes in liver tissue and the possible mechanisms of pesticide-induced hepatotoxicity [ 40 , 109 ]. In the current study, the control rats showed a normal liver architecture while the livers of the rats receiving low and medium doses of IM or CPF showed mild liver damage with some inflammatory cells, enlarged sinusoids, and condensed nuclei.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Before exposure to the FPN inhalation, the animals were relaxed with minimum handling stress with no estimated adverse effect level by the operating and handling approaches adopted as reported in the study. 23 …”
Section: Methodsmentioning
confidence: 99%